Bilateral Anterior Capsulotomy for the Treatment of Refractory Somatic Symptom Disorder: A Case Report - Weibin He; Lingmin Shao; Huiling Wang; Huan Huang; Shudi Zhang; Chenhui Li; Chencheng Zhang; Chencheng Zhang; Wei Yi (Frontiers in Integrative Neuroscience, 2022)
Somatic symptom disorder (SSD) is a form of mental illness that causes one or more distressing somatic symptoms leading to a significant disruption to everyday life, characterized by excessive thoughts, feelings, or behaviors related to these symptoms. While SSD is characterized by significant discomfort in some parts of the body, these symptoms are not related to any known medical condition and therefore it cannot be diagnosed using any medical instrument examination. Currently available treatments for SSD, including drug therapy and psychotherapy (such as cognitive behavioral therapy), usually improve psychiatric symptoms, but the results are often disappointing. Furthermore, SSD is often comorbid with anxiety and depression (75.1 and 65.7%, respectively). Importantly, interventions targeting the anterior limb of the internal capsule (ALIC; e.g., deep brain stimulation and thermal ablation) can effectively treat various mental disorders, such as refractory obsessive-compulsive disorder, depression, and eating disorders, suggesting that it may also be effective for treating the depressive symptoms associated with SSD comorbidity. In this report, a 65-year-old woman diagnosed with SSD accompanied with depression and anxiety underwent bilateral anterior capsulotomy. The patient complained of nausea and vomiting, swelling of the hilum of the liver for 14 years, weakness of the limbs for 13 years, and burning pain in the esophagus for 1 year. Psychiatric and neuropsychological assessments were conducted to record the severity of the patients' symptoms and the progression of postoperative symptoms. The patient's somatization, depression, and anxiety symptoms as well as quality of life improved significantly and steadily; thus, anti-depressive and anti-anxiety medication were stopped. However, the patient developed new somatization symptoms, including dizziness, headache, and sternal pain, 10 months after the operation. Therefore, the patient resumed taking flupentixol and melitracen in order to control the new symptoms. This study shows that bilateral anterior capsulotomy appears to be a complementary treatment for refractory SSD with depressive and anxiety symptoms. Furthermore, postoperative use of anxiolytic and antidepressant medications may be useful for controlling future somatization symptoms.